(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Romashchenko I. V. Professional culture of teacher as a condition of self-actualization of educator. The thesis is concerned with the problem of future tearchers communicative skills as the main sourse of instolation Europinian standarts in studing and teaching process of modern education. The theoretical analysis of the research problem from the point to Psychology and Pedagogy is made. The main approaches to the definition of the term «communication» and «communicative skills» are written. Sufficient pedagogical conditions and methods for forming communicative skills are defined by the author.